Focal adhesion kinase promotes ribosome biogenesis to drive advanced thyroid cancer cell growth and survival - Kellett, Meghan D.; Sharma, Vibha; Sherlock, Madeline E.; Pugazhenthi, Umarani; Rose, Madison M.; Joshi, Molishree U.; Dzieciatkowska, Monika; Nguyen, Vu; Reigan, Philip; Hansen, Kirk C.; Kieft, Jeffrey S.; Schweppe, Rebecca E. (Frontiers in Oncology, 2025)
IntroductionAdvanced thyroid cancer, including papillary (PTC) and anaplastic thyroid cancer (ATC), are the leading causes of endocrine cancer deaths. Thus, there is a critical need to identify novel therapeutic targets to improve standard of care. Focal Adhesion Kinase (FAK) is overexpressed and phosphorylated in thyroid cancer and drives thyroid cancer growth, invasion, and metastasis. FAK is a nonreceptor tyrosine kinase that is autophosphorylated at tyrosine 397 (Y397) in response to integrin or growth factor receptor signaling, resulting in the recruitment of SRC proto-oncogene and downstream signaling pathways. FAK is predominately localized at the plasma membrane but has recently been shown to accumulate in the nucleus as well as the nucleolus to drive tumor growth. The nucleolus is a membraneless subnuclear organelle that is involved in ribosomal biogenesis through the transcription, processing, and assembly of ribosomal RNA (rRNA). The role of FAK in ribosome biogenesis is currently unknown.MethodsNuclear/nucleolar FAK localization and function were studied using genetic and pharmacological approaches. High resolution microscopy was used to study the subcellular localization of FAK. Functional and biochemical assays including transformation and clonogenic assays, polysome profiling, and nascent protein synthesis assays were utilized to assess cell growth and survival. Protein-protein interactions of FAK were determined using a proximity dependent biotinylation (BioID) proteomics approach.ResultsWe have found that pY397 FAK accumulates in the nucleolus of advanced thyroid cancer cells and that autophosphorylation of FAK at pY397 and FAK kinase activity are important for nucleolar accumulation of FAK. Furthermore, knockdown of nucleophosmin 1 (NPM1), an important structural component of the nucleolus, reduced pY397 FAK nucleolar accumulation. Functionally, we showed that nuclear FAK and FAK kinase activity are necessary for anchorage independent growth. We demonstrated that targeted degradation of FAK results in decreased protein synthesis with a specific decrease in the 60S ribosomal subunit. Using a BioID proteomics approach, we showed that autophosphorylated FAK interacts with a network of nucleolar proteins including nucleolar protein 56 (NOP56) which is a core small ribonucleoprotein (snoRNP) important for 60S ribosome biogenesis. Finally, we found that pY397 FAK co-localizes with NOP56 and that knockdown of NOP56 phenocopies FAK depletion.ConclusionsOverall, these findings highlight a novel function for FAK in promoting ribosome biogenesis and suggest that nucleolar FAK represents a promising therapeutic target.